Análisis de sostenibilidad del ciclo de vida de la expansión de energía en Brasil - Gabriel Lassio, João; Matos, Denise; Castelo Branco, David; Magrini, Alessandra (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
The sustainable development paradigm has been encouraging the current worldwide transition from fossil fuels torenewable energy sources and a more balanced approach to the social-environmental concerns against economic hegemony, which implies changes in how decision-makers design the future electricity system. In this context, this paper explores the integration of the Life Cycle Sustainability Assessment (LCSA) with a Multicriteria Decision Making (MCDM)method, named Simple Multi-Attribute Rating Technique Exploiting Ranks (SMARTER), in order to analyze and compare the sustainability performance of the current electricity mix with different future scenarios in Brazil, reported by The Brazilian Ten-Year Energy Expansion Plan 2027. This analysis considers nine criteria distributed into environmental, social,and economic dimensions of sustainability obtained from different sources, such as literature, the Ecoinvent 3.5 database, and calculated by ReCiPe 2016 and USEtox 2 methods. According to the results, the current electricity mix presents the best social and economic performance, and its environmental performance will enhance in the future, mainly due to the expansion of some renewable energy sources. Concerning the future scenarios investigated, the results indicate that those with greater participation from these energy sources are associated with the best sustainability performance. However, it isworth pointing out that these results do not represent the most suitable Brazilian electricity mix path. Besides the criteriaconsidered in this paper, it is influenced by other factors, such as technical, geographical, and national policy. Furthermore, assuming different suppositions and system boundaries for energy sources and technologies might significantly vary our findings.